Utilization of peritoneal dialysis in the acute setting - Gabriel, Daniela Ponce [UNESP]; Fernández-Cean, Juan; Balbi, André Luis [UNESP] (SAGE Publications, 2007)
Peritoneal dialysis (PD), although classically described and utilized in the treatment of patients with end-stage renal disease, can also be utilized in the acute setting in different clinical situations. Recent studies showed that, in patients with acute renal failure, it is possible to obtain reasonable dialysis doses with adequate metabolic and electrolytic control and low incidence of complications by utilizing continuous PD through a cycler at high volume. In patients with congestive heart failure without end-stage renal disease, PD is capable of promoting clinical improvement with slow removal of liquids, becoming an attractive alternative for situations of rapidly or slowly worsening cardiac function. In patients submitted to chronic hemodialysis but who have vascular access difficulties, PD can also be utilized as a bridge, thereby avoiding the use of central venous catheters, which can be associated with infectious complications such as bacterial endocarditis. New studies must be realized showing other indications for PD. Copyright © 2007 International Society for Peritoneal Dialysis.
Keywords: Acute renal failure; Congestive heart failure; End-stage renal disease